Genetic determinants of activity and antigen levels of contact system factors. (2nd November 2018) - Rohmann, J. L.; de Haan, H. G.; Algra, A.; Vossen, C. Y.; Rosendaal, F. R.; Siegerink, B.
Abstract : Essentials Genetic variation may provide valuable insight into the role of the contact system in thrombosis. Explored associations of genetic variants with activity, antigen, and disease in RATIO study. Two novel loci were identified: KLKB1 rs4253243 for prekallikrein; KNG1 rs5029980 for HMWK levels. Contact system variants and haplotypes were not associated with myocardial infarction or stroke. Summary: Background: The complex, interdependent contact activation system has been implicated in thrombotic disease, although few genetic determinants of levels of proteins from this system are known. Objectives: Our primary aim was to study the influence of common F11, F12, KLKB1, and KNG1 variants on factor (F) XI activity and FXI, FXII, prekallikrein (PK) and high‐molecular‐weight kininogen (HMWK) antigen levels, as well as the risk of myocardial infarction and ischemic stroke. Patients/methods: We analyzed samples from all 630 healthy participants, 182 ischemic stroke patients and 216 myocardial infarction patients in the RATIO case–control study of women aged < 50 years. Forty‐three tagging single nucleotide variants (SNVs) were genotyped to represent common genetic variation in the contact system genes. Antigen and activity levels were measured with sandwich‐ELISA‐based and one‐stage clotting assays. We performed single variant, age‐adjusted, linear regression analyses per trait and disease phenotype, assuming additive inheritance and determined conditionally independent associations. Haplotypes based on the lead SNV and all conditionally independent SNVs were tested for association with traits and disease. Results: We identified two novel associations of KLKB1 SNV rs4253243 with PK antigen (βconditional = −12.38; 95% CI, −20.07 to −4.69) and KNG1 SNV rs5029980 with HMWK antigen (βconditional = 5.86; 95% CI, 2.40–9.32) and replicated previously reported associations in a single study. Further analyses probed whether the observed associations were indicative of linkage, pleiotropic effects or mediation. No individual SNVs or haplotypes were associated with the disease outcomes. Conclusion: This study adds to current knowledge of how genetic variation influences contact system protein levels and clarifies interdependencies.